Enhancing Nitric Acid Production Efficiency Using Tail Gas Recycle - Daffa Rahmatullah Ruslan; Hillary Nadine Lerrick; Krisnelly Theni; Monika Silviana; Samuel Octavianus Hasiholan Simangunsong (Journal of Chemical Engineering Research Progress, 2025)
This study simulates and compares the conventional Ostwald process, and a modified full tail-gas recycle configuration to evaluate the enhancement in nitric acid production efficiency. Using simulation software with the Peng–Robinson model, the conventional Ostwald process and a modified recycle configuration were simulated and compared. In the standard process, unabsorbed NO₂ leaves with the tail gas, limiting nitric acid formation. Recycling this tail gas back to the absorber increases NOx contact time and promotes further conversion. Process efficiency, evaluated through production intensity (PI), improved from 0.4702 to 1.0320 kg HNO₃ per kg NH₃, a 119% increase. These results show that tail-gas recycling is an effective and straightforward method to boost nitric acid yield and reduce emissions without significant changes to the existing flowsheet. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).